The myths surrounding mild stimulation in vitro fertilization (IVF) - Raoul Orvieto; Valeria Stella Vanni; Norbert Gleicher (BMC, 2017)
Abstract So-called mild controlled ovarian hyperstimulation (mCOH) has in recent years increased in popularity, claiming to be safer and more patient-friendly, while also improving in vitro fertilization (IVF) outcomes. We here challenge the International Society for Mild Approaches in Assisted Reproduction (ISMAAR) definition of mild stimulation, and especially address four fundamental issues, where our review found conventional COH (cCOH) advantageous over mCOH. They are: prevalence of severe ovarian hyperstimulation syndrome (OHSS), oocyte/embryo quality, pregnancy/live birth rates, and cost. We conclude that an objective review of the literature does not support the routine utilization of mCOH in assisted reproduction.